Comparaison in vitro de trois systèmes d’irrigation : EndoVac, RinsEndo et Seringue pour l’élimination des débris intracanalaires - Micha KABALAN; Alfred NAAMAN; Walid NEHMÉ (International Arab Journal of Dentistry (IAJD), 2010)
The anatomical complexity of the canal system tends to reduce the tissue-dissolving capacity and antibacterial effect of sodium hypochlorite especially in the apical zone of the root canal. Several means of irrigation were used during the last decade. Among the three systems tested in this study, RinsEndo showed the most satisfactory results as for the elimination of the dentinal debris on the apical third.